2009
DOI: 10.1016/j.cub.2009.06.066
|View full text |Cite
|
Sign up to set email alerts
|

VA Opsin-Based Photoreceptors in the Hypothalamus of Birds

Abstract: Studies in the 1930s demonstrated that birds possess photoreceptors that are located within the hypothalamus and regulate photoperiodic responses to day length. Most recently, photoperiod has been shown to alter the activity of the pars tuberalis to release thyrotrophin, which ultimately drives a reproductive response. Despite these significant findings, the cellular and molecular identity of the hypothalamic photoreceptors has remained a mystery. Action spectra implicated an opsin-based photopigment system, b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
135
1
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 151 publications
(140 citation statements)
references
References 39 publications
3
135
1
1
Order By: Relevance
“…Foster et al, Foster and Follett, and Halford et al reported an action spectrum for the photoperiodic response in quail with a λ max of ≈483-492 nm (9,10,16). Careful analysis of their results, however, revealed that light with a wavelength of 410 nm also caused a photoperiodic response.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Foster et al, Foster and Follett, and Halford et al reported an action spectrum for the photoperiodic response in quail with a λ max of ≈483-492 nm (9,10,16). Careful analysis of their results, however, revealed that light with a wavelength of 410 nm also caused a photoperiodic response.…”
Section: Discussionmentioning
confidence: 99%
“…Expression of melanopsin has been demonstrated in the lateral septal region as well as the retina and pineal gland in chicks (15). Recently, vertebrate ancient (VA) opsin-like immunoreactivity was detected in the avian anterior hypothalamus (16). Although spectral sensitivities of avian melanopsin and VA opsin remain to be determined, both mammalian melanopsin and teleost VA opsin have a λ max of ∼480 nm (44,45).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, it remains a possibility that the UV and blue wavelengths tested by Nakane et al (2) stimulated testis growth through photopigments other than Opn5. As previously mentioned, VA-opsin has indeed been identified in the developing (19) and adult avian brain (11); it has also been suggested (albeit not tested) that a TSH-mediated photoperiodic response, virtually identical to the one presented by Nakane et al (2), is initiated by VA-opsin activation (11).…”
Section: Nakane Et Al Aggregatementioning
confidence: 90%
“…Rhodopsin-like immunoreactivity was initially observed in the tuberal hypothalamus and septal forebrain regions of the pigeon (8,9). Later studies indicated that melanopsin and vertebrate ancient opsin (VA-opsin) were found in the avian brain (10,11).…”
Section: History Of Encephalic Photoreceptionmentioning
confidence: 95%